2015
DOI: 10.1016/j.midw.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

An explorative study of factors contributing to the job satisfaction of primary care midwives

Abstract: our knowledge, our study is the first explorative study on factors associated with job satisfaction of primary care midwives. While there are several studies on job satisfaction in health care; little is known about the working conditions of midwives in primary care settings. Although the participating primary care midwives in the Netherlands were satisfied with their job, areas for improvement were identified. The results of our study can be relevant for countries that have a comparable obstetric system as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 20 publications
2
32
0
2
Order By: Relevance
“…Results revealed that the overall mean of job satisfaction among Jordanian midwives was neither satisfied nor dissatisfied. Studies from other countries reported that midwives showed a moderate level of job satisfaction, including Iran (Khavayet et al 2018; Rahimparvar et al 2017), the Netherlands (Warmelink et al 2015), Ethiopia (Bekru et al 2017) and Turkey (Ucuk & Yurtsal 2017). Therefore, the level of satisfaction of Jordanian midwives is similar to midwivesin a number of countries.…”
Section: Discussionmentioning
confidence: 99%
“…Results revealed that the overall mean of job satisfaction among Jordanian midwives was neither satisfied nor dissatisfied. Studies from other countries reported that midwives showed a moderate level of job satisfaction, including Iran (Khavayet et al 2018; Rahimparvar et al 2017), the Netherlands (Warmelink et al 2015), Ethiopia (Bekru et al 2017) and Turkey (Ucuk & Yurtsal 2017). Therefore, the level of satisfaction of Jordanian midwives is similar to midwivesin a number of countries.…”
Section: Discussionmentioning
confidence: 99%
“…It also indicated that registered midwives were not satisfied with the high percentage of shortage in their units. Warmelink, Hoijtink, Noppers, Wiegers, Paul de Cock et al [12]. showed that in Tanzania, perinatal morbidities are problems of public health importance, and have been linked to the shortage of skilled staff.…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of registered midwives indicated that there were not satisfied with resignation rates in their units, as it results in shortage of staff. Warmelink et al [12]. noted that job satisfaction plays an important part in any decision to leave the job.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity toward the stakeholders as a human resource was paramount. Dutch midwives perceive their workloads to be high . This resulted in a choice to use individual interviews and written feedback, rather than organizing group interviews for the midwife and student midwife stakeholders.…”
Section: Reflections On This Process: Lessons Learnedmentioning
confidence: 96%